(untitled) (Al-Farooq Journal of Sciences, 2025)
The study examined the concept of the universal reason and natural law in Stoic philosophy according to Zeno of Citium through an analytical philosophical reading that reveals the relationship between the cosmic and ethical dimensions of Stoicism. The study showed that universal reason represents the organizing principle of nature and the cosmos, and that it is not separate from the world, but an immanent principle that pervades beings and grants them unity and order. It also clarified that natural law is the ethical and practical expression of this universal reason, guiding human beings to live according to nature, reason, and virtue. The study concluded that Zeno’s Stoic ethics are based on controlling passions, accepting necessity, and aligning human will with the rational cosmic order.